Student’s self-confidence in practicing speaking during online learning: up or down? - Rozy Khanafiyah; Reza Adinul Akbar; Dewi Puspitasari (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2021)
The research aims to investigate students' self-confidence in online speaking practice during the Covid-19 pandemic. The synchronous and asynchronous platforms of learning have been used to accommodate the learning process thus students can practice communicating in non-face-to-face meetings. This qualitative research documents the learning experiences of six EFL students of the English Department at a public university in Central Java, Indonesia. By taking a purposive sampling technique, the researchers started the study by collecting participants’ data through an interview. The results of this study prove that four participants experienced a decrease in self-confidence due to the following factors. First, the practice of speaking through digital media makes it difficult for them to practice face-to-face communication. Second, the lack of understanding in the debate material, and the influence of social relations in a hostile home environment (parental variation). However, two students who have strong and high resilience, motivation, self-efficacy, can overcome these challenges.